Implementation of the Theory of Planned Behavior (TPB) in Student Career Planning at Nias Regional Private Vocational High School - Firwanus Zega; M. Giatman; Ambiyar; Dedy Irfan (Jurnal Penelitian Pendidikan IPA, 2025)
There is a gap between the objectives of secondary education programs and the current unemployment rate in Indonesia. Vocational High School (SMK) graduates, equipped with work knowledge and skills, still contribute significantly to the unemployment rate in Indonesia. Career guidance is essential, especially as initial preparation for entering the workforce for vocational high school students, as students still face challenges, such as deciding whether to work immediately or continue their studies at university after graduation. All these issues highlight the need for a more comprehensive approach to supporting students' career choices. This study aims to examine the effect of implementing the Theory of Planned Behavior (TPB) on career planning among students at SMK Swasta Pembda Nias. The three main components of TPB were analyzed in this study: attitude toward behavior, subjective norms, and perceived behavioral control. A quantitative approach using a correlational survey method was employed, with data analyzed through simple and multiple regression techniques. The population comprised all students of SMK Swasta Pembda Nias, with samples taken using random sampling techniques. The findings indicate that each variable (attitude, subjective norm, and perceived control of behavior) has a significant effect on students' career planning. Furthermore, these three variables simultaneously influence career planning significantly. These results suggest that the implementation of TPB is an effective approach to guide career counseling strategies, especially in rural vocational school settings such as Nias.